Novel allosteric inhibitor to target drug resistance in EGFR mutant: molecular modelling and free energy approach - Singh A.; Saini R.; Mishra A. (My University, 2025)
Anticancer therapy targets Tyrosine kinase (TK) to inhibit signal transduction pathway that regulate various physiological and biochemical processes. Mutation in and around the catalytic domain may lead to conformational changes and activity. The first identified mutation leading to resistance against tyrosine kinase inhibitor (TKI) was observed when Thr at 790 replaced to Met in Epidermal Growth Factor Receptor (EGFR). Third generation EGFR-TKIs bind irreversibly to the Cysteine 797, (ATP-binding pocket). Mutation of Cys 797 to Ser residue (EGFRC797S) causes resistance to third generation TKI. The present study explores allosteric inhibitor of EGFRT790M+C797S mutant TK by molecular modelling techniques using 3,92,945 compounds of Zinc database. Molecular docking study revealed that ZINC000072404720 have similar binding pattern and MM/GBSA free energy as known allosteric inhibitor EAI045. RMSD of EGFRT790M+C797S bound to EAI045 and ZINC000072404720 were quite similar and in acceptable range. Hydrogen bonds after 150ns simulation was observed between Lys 745 and Asp 855 with EAI045 and novel inhibitor showed hydrogen bonding with Lys 745, Leu 788, Thr 854, Asp 855, Phe 856. MM/GBSA free energy was better (-84.09 Kcal/mol) known inhibitor EAI045b (-65.95 Kcal/mol). ZINC000072404720 fulfils drug likeliness property and did not violate Lipinski’s rule of five. © 2022 Informa UK Limited, trading as Taylor & Francis Group.